2021
DOI: 10.7717/peerj.11579
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mental and somatic stressors on physical activity and sedentary behaviour in adults with type 2 diabetes mellitus: a diary study

Abstract: Background Adopting an active lifestyle is key in the management of type 2 diabetes mellitus (T2DM). Nevertheless, the majority of individuals with T2DM fails to do so. Additionally, individuals with T2DM are likely to experience mental (e.g., stress) and somatic (e.g., pain) stressors. Research investigating the link between these stressors and activity levels within this group is largely lacking. Therefore, current research aimed to investigate how daily fluctuations in mental and somatic stressors predict d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…If normality could not be assumed, the Bayesian Information Criterion (BIC) of models with different variance and link functions (i.e. Gamma with log, Gamma with identity, Poisson with log, and negative binomial with log) were compared and the model with the lowest BIC value was selected (Germeys & De Gieter, 2018; Poppe et al, 2021). The content of the goals (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…If normality could not be assumed, the Bayesian Information Criterion (BIC) of models with different variance and link functions (i.e. Gamma with log, Gamma with identity, Poisson with log, and negative binomial with log) were compared and the model with the lowest BIC value was selected (Germeys & De Gieter, 2018; Poppe et al, 2021). The content of the goals (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…time-dependent) variables that vary from day to day and even throughout the day (Dunton et al 2010). Indeed, research already showed that PA is in uenced by how we feel in the moment and how we interact with our environment (Dunton 2017;Poppe et al 2021). For example, several studies (Dunton et al 2010;Schultchen et al 2019;Vetrovsky et al 2021) demonstrated that emotions and physical complaints (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ifnormality could not be assumed, the Bayesian Information Criterion (BIC) of models with different variance and link functions (i.e. Gamma with log, Gamma with identity, Poisson with log, and negative binomial with log) were compared and the model with the lowest BIC value was selected (Germeys & De Gieter 2018;Poppe et al 2021). The content of the goals (i.e.…”
mentioning
confidence: 99%